Revisión sobre el hongo microcyclus ulei, agente causal del mal suramericano de la hoja del caucho (2006)
The Microcyclus ulei Ascomycetes fungus is the causal agent of south-American leaf blight (SALB), this being one of the most important diseases affecting the natural rubber tree (Hevea brasiliensis) in Latina-America and has been responsible for numerous economic losses. This fungus has presented high physiological variability, suggesting its great adaptability. HCN tolerance has been described as being one of the mechanisms associated with its virulence. Resistant Hevea clones have been obtained by genetic improvement; however, the mechanisms associated with this are still not well known. Greater knowledge of this pathogen will lead to developing new control strategies and better understanding of the mechanisms associated with host resistance. Key words: Microcyclus ulei, SALB, Hevea brasiliensis.